Guided Bone Regeneration Using a Modified Occlusive Barrier with a Window: A Case Report - Luis Leiva-Gea; Alfonso Lendínez-Jurado; Paulino Sánchez-Palomino; Bendición Delgado-Ramos; María Daniela Corte-Torres; Isabel Leiva-Gea; Antonio Leiva-Gea (Biomimetics)
Background: Bone resorption following tooth loss poses significant challenges for dental implant success. Guided bone regeneration (GBR) techniques, particularly in vertically deficient ridges, often require complex procedures and soft tissue management. This case report introduces a modified occlusive barrier with a window, combined with tricalcium phosphate, to address these challenges. Methods: A 26-year-old female with significant bone loss in the mandibular anterior region underwent GBR using a digitally designed titanium occlusive barrier. The barrier was fabricated using CAD/CAM technology and secured with screws. A blood clot mixed with tricalcium phosphate was used to promote bone regeneration. Postoperative care included regular irrigation, de-epithelialization, and follow-up over six months. Implant placement and histological analysis were performed to evaluate outcomes. Case Presentation: The patient achieved 8.8 mm of vertical and 7.6 mm of horizontal bone regeneration. Histological analysis confirmed the presence of mature, mineralized bone, and keratinized gingiva. The implant was successfully placed, and a fixed prosthesis was restored after four months, with stable results at a three-year follow-up. Conclusion: This technique demonstrates effective bone and soft tissue regeneration in a single procedure, eliminating the need for autologous bone grafts and secondary surgeries. The use of a digitally designed occlusive barrier offers precision, reduces morbidity, and simplifies the surgical process, suggesting a promising advancement in GBR. Further studies are needed to validate these findings.